Clinical and Microbiological Characteristics of Carbapenem-Resistant Klebsiella pneumoniae Associated Recurrent Urinary Tract Infections - Cao H; Cheng H; Zhou J; Zhao J; Xu M; Fei Y (Infection and Drug Resistance)
Huijun Cao,1,2,* Hang Cheng,3,* Jing Zhou,3 Jiyuan Zhao,3 Mei Xu,1 Ying Fei1 1Center for Clinical Laboratories, the Affiliated Hospital of Guizhou Medical University, Guiyang, People’s Republic of China; 2College of Life Sciences, Fujian Normal University, Fuzhou, People’s Republic of China; 3School of Clinical Laboratory Science, Guizhou Medical University, Guiyang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ying Fei, Center for Clinical Laboratories, the Affiliated Hospital of Guizhou Medical University, Guiyang, 550004, People’s Republic of China, Email feiying@gmc.edu.cnBackground: Carbapenem-resistant Klebsiella pneumoniae (CRKP) is a major pathogen responsible for urinary tract infections (UTIs). However, its role and characteristics in recurrent urinary tract infections (rUTIs) remain poorly understood. Investigating its features in rUTIs may provide insights into effective prevention strategies.Methods: We analyzed a cohort of patients with rUTIs caused by Klebsiella pneumoniae from April 2020 to April 2024. Antibiotic susceptibility of the isolates was evaluated. Biofilm Formation Assay and Galleria mellonella infection models were employed to assess the virulence of the strains. Polymerase Chain Reaction (PCR) and whole-genome sequencing (WGS) were utilized to determine multilocus sequence typing (MLST) and capsular serotyping, as well as to identify resistance genes, virulence genes, and plasmid replicons. Phylogenetic relationships among the isolates were also established.Results: A total of 41 patients with rUTIs were included, with 56.1% caused by CRKP. 97.01% of CRKP carry the blaKPC-2 gene. Compared to patients infected with carbapenem-susceptible Klebsiella pneumoniae (CSKP), those infected with CRKP had a higher prevalence of underlying diseases and complications. Both groups of strains exhibited a high degree of antibiotic resistance. CRKP strains demonstrated enhanced biofilm formation capacity and greater lethality in Galleria mellonella infection models. The predominant phenotype of the CRKP strain was ST11 KL64, whereas the CSKP strain showed multiple phenotypes in different patients. Sequencing analyses revealed that both groups of strains carried a wide range of virulence genes, resistance genes, and plasmid replicons. Among the cases of rUTIs, 31 were identified as relapses caused by the same strain, with no significant differences between the initial and final infection strains.Conclusion: This study demonstrates that patients with rUTIs caused by CRKP present significant complexity in terms of clinical features, strain resistance and virulence properties. When managing UTIs caused by CRKP, special care needs to be taken to manage recurrent infections.Keywords: recurrent urinary tract infections, carbapenem-resistant Klebsiella pneumoniae, antibiotic resistance, virulence, whole genome sequencing